2017
DOI: 10.11604/pamj.2017.26.180.9637
|View full text |Cite
|
Sign up to set email alerts
|

Current problematic and emergence of carbapenemase-producing bacteria: a brief report from a libyan hospital

Abstract: A collection of 94 Gram-negative bacteria isolates, showing different antimicrobial resistance phenotypes including to the carbapenem classes was investigated. Strains were originated form clinical sources from a single hospital in Tripoli, Libya during 2015 and were identified based on cultural and phenotypic characteristics, and fully characterized by the VITEK automated system. Forty-eight percent (48%) of the collection was identified as Acinetobacter baumannii, 50% Klebsiella pneumoniae and 2% Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, a similar study at MBRRH detected lower phenotypic prevalence of 12.6% [ 25 ]. Contrary to this, studies in North Africa and West Africa reported remarkably higher phenotypic resistance of > 50% and K. pneumoniae were the most prevalent isolates [ 26 29 ]. Furthermore, a larger study which covered Gauteng, KwaZulu-Natal, Western Cape and Free State provinces in South Africa documented overwhelming phenotypic resistance of between 47 and 50% to imipenem, meropenem and doripenem, 84% and 89% to ertapenem [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 96%
“…However, a similar study at MBRRH detected lower phenotypic prevalence of 12.6% [ 25 ]. Contrary to this, studies in North Africa and West Africa reported remarkably higher phenotypic resistance of > 50% and K. pneumoniae were the most prevalent isolates [ 26 29 ]. Furthermore, a larger study which covered Gauteng, KwaZulu-Natal, Western Cape and Free State provinces in South Africa documented overwhelming phenotypic resistance of between 47 and 50% to imipenem, meropenem and doripenem, 84% and 89% to ertapenem [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 96%
“…However, a similar study at MBRRH detected lower phenotypic prevalence of 12.6% [25]. Contrary to this, studies in North Africa and West Africa reported remarkably higher phenotypic resistance of > 50% and K. pneumoniae were the most prevalent isolates [26][27][28][29]. Furthermore, in a larger study which covered Gauteng, KwaZulu-Natal, Western Cape and Free State provinces in South Africa documented overwhelming phenotypic resistance of between 47-50% to Imipenem, Meropenem and Doripenem, 84%…”
Section: Discussionmentioning
confidence: 80%
“…antimicrobial susceptibility tests). This is a very serious medical and health concern considering the recent documentation of the alarming emergence of antimicrobial resistance in various bacterial organisms in Libya [9][10][11]. In addition, studies that investigate the role of animals as a source of zoonotic and antimicrobial resistance organisms are rare in/from Libya however, 324 recent evidences have revealed the role of various animal species as a source of emerging bacterial and antimicrobial resistant pathogens such as staphylococci, Salmonella and E.coli 0157 [6,12].…”
Section: Results and Analysismentioning
confidence: 99%